Enhancing specific capacitance and energy density in printed supercapacitors: The role of activated wood carbon and electrolyte dynamics - Pourkheirollah, Hamed; Vitto, Remuel Isaac M.; Volperts, Aleksandrs; Vindt, Steffen Thrane; Grīnberga, Līga; Kučinskis, Gints; Keskinen, Jari; Mäntysalo, Matti (Elsevier Ltd, 2025)
This study investigates Activated Wood Carbon (AWC) as an electrode material for advancing printed supercapacitors (SCs). AWC, derived from biomass, offers a sustainable alternative to conventional activated carbons. The research highlights the interplay between AWC's structural properties and electrolyte compatibility, addressing challenges in energy storage technologies. Comprehensive analyses, including sorptometry, Raman spectroscopy, X-ray diffraction (XRD), and electrochemical assessments, reveal that AWC's graphitization and structural ordering significantly influence its performance. Printed SCs fabricated with AWC demonstrate superior performance compared to those using benchmark Kuraray YP-80F activated carbon, achieving up to 93 % and 90 % higher specific capacitance and energy density at 1.0 V and 1.2 V, respectively. The enhanced performance is attributed to AWC's increased surface area and pore volume, which provide abundant ion storage sites and improve ion mobility. Furthermore, the porous structure of AWC facilitates better compatibility with KxHyPO4 electrolytes compared to NaCl, with pseudocapacitive effects also contributing to the improved energy storage behavior. This work underscores the potential of biomass-derived carbon materials in creating high-performance, sustainable SCs. Future efforts will focus on optimizing electrode and electrolyte configurations to further enhance device performance, supporting the transition toward renewable energy solutions. © 2024 The Author(s) --//-- This is an open-access article Hamed Pourkheirollah, Remuel Isaac M. Vitto, Aleksandrs Volperts, Steffen Thrane Vindt, Līga Grīnberga, Gints Kučinskis, Jari Keskinen, Matti Mäntysalo, Enhancing specific capacitance and energy density in printed supercapacitors: The role of activated wood carbon and electrolyte dynamics, Carbon Trends, Volume 18, 2025, 100436, ISSN 2667-0569, https://doi.org/10.1016/j.cartre.2024.100436 published under the CC BY-NC-ND licence.
This project, funded by the European Commission's Horizon Europe programme, is part of the Graphene Flagship initiative which works to advance technologies that rely on graphene and other 2D materials. Part of the research uses Academy of Finland Research Infrastructure 'Printed Intelligence Infrastructure' (PII-FIRI, Grant Number 358618). SEM images were obtained by Ph.D. Guna Krieķe at the Insitute of Solid State Physics, University of Latvia that has received funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Activated wood carbon; Energy density; Energy storage; Graphitization; Printed supercapacitors; Specific capacitance